2021
DOI: 10.1111/puar.13413
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Empirical Research on the Impacts of e‐Government: A Public Value Perspective

Abstract: While government organizations continue to invest in e‐Government systems, there is still uncertainty as to the benefits that can be generated. Without clear expectations, it will be impossible for managers to measure and evaluate outcomes. This systematic literature review examines 60 empirical studies on the impacts of e‐Government published in the leading public administration and information systems journals. The impacts are classified using public value theory, first, by the role for whom value is generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 120 publications
(277 reference statements)
0
30
0
2
Order By: Relevance
“…Public administration and policy are at the center of a wave of intensive attention and participation. Prior literature has explored opportunities for public participation (Fung, 2015; Handley & Howell‐Moroney, 2010), citizen engagement (Cooper, 2005), coproduction (Bovaird et al, 2021), and participatory and e‐government (MacLean & Titah, 2021). However, the transition from government to governance—that is, less concern with formal structure and greater focus on informal approaches to overcoming barriers and solving problems—has quickly moved the literature in a new direction.…”
Section: Advancements In Public Administrationmentioning
confidence: 99%
“…Public administration and policy are at the center of a wave of intensive attention and participation. Prior literature has explored opportunities for public participation (Fung, 2015; Handley & Howell‐Moroney, 2010), citizen engagement (Cooper, 2005), coproduction (Bovaird et al, 2021), and participatory and e‐government (MacLean & Titah, 2021). However, the transition from government to governance—that is, less concern with formal structure and greater focus on informal approaches to overcoming barriers and solving problems—has quickly moved the literature in a new direction.…”
Section: Advancements In Public Administrationmentioning
confidence: 99%
“…Some have indicated that the creation of public value for people/citizens via services hinges on quality standards such as obtainability of service, satisfaction levels, prominence, issues of fairness, and cost (Cordella and Bonina, 2012 ; Karkin and Janssen, 2014 ). Since e-government is based on the provision of citizen-centered programs and actions of government, the measurement and assessment of the public value of e-government concerning the public value generated should also be citizen-centered (Picazo-Vela et al, 2018 ; Chohan et al, 2020 ; MacLean and Titah, 2021 ). E-government is projected as means to determine and increase the public value created by public management systems which indirectly means that e-government strategies can better be measured as per their potential to intensify the public governance capacity of generating public value (Savoldelli, 2013 ; Picazo-Vela et al, 2015 ; Lindgren and van Veenstra, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence the proposed PVEGAM is to provide a framework that contributes to an effective performance evaluation of e-government projects to deliver e-government outcomes that will drive the adoption of e-government services. While previous studies have discussed the concept of public value in the context of e-government (Valle-Cruz, 2019 ; Bouaziz, 2020 ; MacLean and Titah, 2021 ; Scupola and Mergel, 2022 ), these studies and other bodies of literature however failed to examine the determinants of public value in the domain of e-government and how the public value of e-government can drive the uptake of e-government services. Consequently, this paper fills the conceptual gap and addresses the need for a specific public value of the e-government adoption model to drive the theoretical and practical underpinnings of e-government development and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the phenomenal expansion of e-government services is well-clinched (Carter et al , 2022), there is still a wide gap between theory and practice in terms of the benefits that might be realized (Dias, 2020a, 2020b; Bwalya et al , 2014; Deakins and Dillon, 2002; MacLean and Titah, 2022; Mutula, 2008; Schedler and Schmidt, 2004; Zahid et al , 2022). E-government websites are sometimes non-interactive and non-deliberative (Torres et al , 2005).…”
Section: Introductionmentioning
confidence: 99%